2019
DOI: 10.1186/s12933-019-0948-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and insulin levels are associated with arterial stiffness and concentric remodeling of the heart

Abstract: BackgroundMortality attributable to heart failure remains high. The prevalence of heart failure in patients with diabetes mellitus ranges from 19 to 26%. It is estimated that up to 21.1 million adults in the United States have diagnosed diabetes mellitus and around 80.8 million have impaired fasting glucose. We investigated the associations of fasting glucose (FG) and fasting insulin (FI), the homeostasis model assessment-insulin resistance index (HOMA-IR) and 2-h postload glucose (2HG) and insulin (2HI) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 41 publications
0
51
0
3
Order By: Relevance
“…Although the exact mechanisms underlying the relationship of the TyG index with arterial stiffness is unclear, it may be linked to IR. IR is associated with hyperinsulinaemia, hyperglycaemia, dyslipidemia, hypertension and a proin ammatory state, as well as the effect of perturbed insulin signaling at the level of the intimal cells (endothelial cells, vascular smooth muscle cells, and macrophages), all of which predispose to arterial stiffness [13,[35][36][37][38]. In our study, men showed larger regression coe cients and odds ratios of the TyG index in relation with increased arterial stiffness than women.…”
Section: Discussionmentioning
confidence: 46%
“…Although the exact mechanisms underlying the relationship of the TyG index with arterial stiffness is unclear, it may be linked to IR. IR is associated with hyperinsulinaemia, hyperglycaemia, dyslipidemia, hypertension and a proin ammatory state, as well as the effect of perturbed insulin signaling at the level of the intimal cells (endothelial cells, vascular smooth muscle cells, and macrophages), all of which predispose to arterial stiffness [13,[35][36][37][38]. In our study, men showed larger regression coe cients and odds ratios of the TyG index in relation with increased arterial stiffness than women.…”
Section: Discussionmentioning
confidence: 46%
“…(2) Study have shown that FBG mainly re ects IR from liver, whereas fasting TGs mainly re ects IR from adipose cell [51]. Therefore, it can be concluded that TyG index may re ect IR from two aspects and thus be closely related to IR, which has been widely demonstrated to have signi cant relationship with endothelial dysfunction, oxidative stress, cardio-vascular remodeling, coagulation imbalance and in ammation response [52][53][54]. Indeed, a positive association between TyG index and hs-CRP levels was con rmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nine adiposity measures were examined in this study: body mass index (BMI; kg/m 2 ), waist circumference (WC; cm), waist-hip ratio (WHR), waist-height ratio (WHtR), body adiposity index (BAI; according to the formula by Reference [23]: (hip circumference (cm))/((height (cm) × 0.01) 1.5 ) − 18), fat mass index (FMI; kg/m 2 ), lean body mass index (LBMI; kg/m 2 ), appendicular muscle mass index (AMMI; kg/m 2 ), and body fat (BF; %). Body composition was measured via bioelectrical impedance analysis (BIA 2000-S device, Data Input, Pöcking, Germany) with Kyle's equations [24][25][26][27]. To enable comparability of results, all adiposity measures were scaled to a mean of 0 and standard deviation of 1 for each (sub-)set for machine learning, separately.…”
Section: Adiposity Measuresmentioning
confidence: 99%